Pemahaman Konseptual Siswa melalui Pemodelan Kebakaran Hutan dan Lahan Gambut: Studi Kasus di Palembang, Sumatera Selatan, Indonesia - Wulandari, Ratu Mutiara; Meilinda, Meilinda; Slamet, Adeng; Putri, Ratu Ilma Indra; Zulkardi, Zulkardi (Universitas Negeri Jakarta, 2025)
Students in South Sumatra are familiar with the direct impacts of forest and peatland fires, yet understanding their connection to global warming remains limited and requires targeted educational interventions. This study investigates conceptual change among 16 students in Palembang after participating in modeling-based learning activities about forest and peatland fires. Although Palembang does not experience such fires directly, the city is heavily affected by the resulting haze, which impacts health, visibility, and daily activities, including school attendance. A qualitative approach was used, and data were collected through multiple-choice questions and student-generated drawings to capture shifts in understanding. The results revealed varied levels of conceptual understanding, categorized as scientific conception from the beginning (37%), static understanding (20%), disorientation (17%), revision or reconstruction (8%), and construction of new understanding (18%). A total of 26% of students demonstrated positive conceptual change after the intervention. These findings suggest that modeling serves as an effective tool to help students visualize complex environmental processes and make connections between local phenomena and global issues. The study highlights the importance of incorporating interactive, visual learning strategies in environmental education to foster deeper, more accurate understanding among students, particularly in areas indirectly affected by ecological disasters. Such approaches can empower students to become more informed and responsible citizens in the face of climate change.